Design Of Web-Based Marketing And Ordering Applications At Talang Permai Store - Fatima Felawati; Jodi Hendrawan; Sepriano Sepriano; Afdalul Zikri (Sustainability (STPP) Theory, Practice and Policy, 2022)
The development of computers is very rapid and the need for information is increasingly perceived existence in an organization, it is no wonder many agencies that use computers to support the operation of these agencies. The emergence of the Internet that increasingly facilitate the exchange of information between users. One of the internet activities in the business world is as a media marketing and product sales through a website. The existence of a website makes it easy for customers to access information about the sale of available building materials and ordering of building materials online for customers at Toko Talang Permai. During this time, the sale and purchase transactions are only done manually and all the information generated about building materials is also not always accurate. With the existence of a marketing and ordering website, it is hoped that Talang Permai Stores can provide the best service to its customers and help facilitate shop owners in terms of data processing. So that the resulting data is more accurate and can increase efficiency and effectiveness. The research methodology used is field research and library research. The design of the Talang Permai socialization and buying and selling media website was made using the PHP programming language and MySql database.